Pharmacotherapy of plexiform neurofibromas in patients with neurofibromatosis type 1. Possible adverse events and their management - A. M. Pivovarova; M. Yu. Dorofeeva; A. R. Zabrodina; S. V. Bochenkov; A. V. Grigoryeva; Z. K. Gorchkhanova; V. R. Voronina (Русский журнал детской неврологии, 2024)
Neurofibromatosis type 1 is a multisystem genetic disorder associated with an increased risk of benign and malignant tumors due to mutations in the NF1 gene. Clinical manifestations of the disease vary and depend on the patient’s age. One of the most common complications of neurofibromatosis type 1 is plexiform neurofibroma – a benign tumor affecting peripheral nerves. For a long time, there had been no standard care for such patients in the Russian Federation; treatment of plexiform neurofibromas was usually limited to symptomatic therapy and repeated surgical interventions. In the last few years, treatment approach to patients with neurofibromatosis type 1 complicated by plexiform neurofibromas changed, since a targeted drug, selumetinib became available. In clinical trials, 65 % of children receiving selumetinib demonstrated a partial response (reduction in the volume of plexiform neurofibromas by 20 % or more) for more than 3 cycles (months), 56 % of children demonstrated a long-term response (a year or more) without traumatic surgical interventions. In our country, more than 200 children have already received selumetinib under the early access program after its registration in the Russian Federation (January 2021). In Yu.E. Veltischev Research and Clinical Institute for Pediatrics and Pediatric Surgery, the drug was prescribed to 104 patients; of them, 54 patients were followed up between April 2021 and October 2023. The most common adverse events associated with selumetinib in our patients included skin rash (acne/maculopapular rash or eczema), dry skin, hair discoloration and hair loss, paronychia, and an asymptomatic elevation of creatine phosphokinase. This article provides information on the most common adverse events of selumetinib therapy, preventive measures, and recommendations for patient follow-up.